Expression patterns of blood-based biomarkers of neurodegeneration and inflammation across adulthood in rhesus macaques - Ludwig A.P. Metzler; Jeanette M. Metzger; Keenan J. Gerred; Marina E. Emborg; Amita Kapoor (Experimental Gerontology)
As the global human population rapidly ages and diseases of aging become more prevalent, preclinical models of age-related neurodegenerative disorders are increasingly important for identifying early diagnostic biomarkers, monitoring disease progression, and evaluating treatment responsiveness. Rhesus macaques are an ideal species for studies on neurodegeneration due to their phylogenetic relatedness to humans and their complex brain anatomy and physiology. Technological advances in assay sensitivity have facilitated the identification of blood-based biomarkers of neurodegeneration and inflammation in human populations. The aim of this study was to translate these methods for use in male and female rhesus macaques across adulthood. We collected plasma samples from 47 rhesus macaques representing pre-adult (1–5 years, n = 6 female, n = 5 male), young (5–7 years, n = 5 female, n = 7 male), middle (8–16 years, n = 7 female, n = 7 male), and older adult (17–22 years, n = 6 female, n = 4 male) subjects. Quantified biomarkers included neurofilament light chain (NfL), glial fibrillary acidic protein (GFAP), amyloid beta (Aβ42, Aβ40, and their ratio), total tau, phosphorylated tau (pTau181), interleukin (IL) 2, IL-6, IL-8, and IL-10. Plasma NfL and IL-6 levels were significantly increased with age in both sexes, with a marked rise during middle adulthood. The ratio of Aβ42/Aβ40 was significantly lower in the middle and older aged females compared to the youngest group. There was no effect of age or sex on total tau or pTau181 levels. Overall, these results demonstrate the feasibility of evaluating blood biomarkers of neurodegeneration and inflammation in rhesus macaques during adulthood.